STRUKTUR MODAL SEKTOR PERBANKAN PADA SAAT KRISIS KEUANGAN - Tuntun Sriwahyuni Darajati; Deny Dwi Hartomo (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2015)
Capital structure is a balance between the use of the capital itself and the debt. It means how much equity and debt to be used, so that it can produce an optimal capital structure. This study aims to determine the effect of internal and external factors on the capital structure of the banking sector during the financial crisis of 2008-2009. Independent variables used are profitability, growth, asset structure, risk, size, liquidity and IHSG. Beside that, IHSG also has the function as a moderating variable.The method that is used for sample research is purposive sampling. It is based on certain criteria. The research was conducted on 72 samples of listed banks in Bank Indonesia, by using the data pooling. It is the combination between time series and the cross section data. Data analysis uses the analysis tools of regression test that was preceded by the classical assumptions, they are normality, multicollinearity, autocorrelation, and heteroscedasticity. Hypothesis test is done by using the F and T test.The result of the data analysis shows that significant profitability, growth, asset structure, risk, size and IHSG that gives the affect to the capital structure of the bank.While liquidity does not affect the bank's capital structure. IHSG has given the proof that it does not moderate the internal variables of the bank's capital structure.